2014
DOI: 10.1016/j.lwt.2013.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of twenty wild Spanish Thymus mastichina L. populations and its relation with their chemical composition

Abstract: The antioxidant activity and chemical composition of essential oils and methanolic extracts of twenty Spanish Thymus mastichina L. populations were studied. Both essential oils and methanolic extracts possessed antioxidant properties. However, the total phenol contents of the methanolic extracts varied between 2.90 and 9.15 mg GAE/g extract and the EC 25 values of DPPH free radical scavenging activity between 0.90 and 3.45 mg/mL for the methanolic extracts and 78e241 mg/mL for essential oils, these showing low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 24 publications
5
41
3
Order By: Relevance
“…So, an anti-anxiety (Kim, Seo, Min, Park, & Seol, 2014), antimicrobial with application as natural preservative in food packaging (Taqi, Askar, Mutihac, & Stamatin, 2013), anti-inflammatory, antiviral or inhibitory of nuclear factor (NF)-kB effect (Li et al, 2016) could be expected with marjoram essence due to high 1,8-cineol (59.59%) content. Our results are in agreement with the percentages obtained from 20 samples of T. mastichina essential oils (1,8-cineol 56.80-69.60%) from Spain (Delgado et al, 2014), and according with ISO quality standards (Table 4) of T. mastichina (Mendez-Tovar, Novak, Sponza, Herrero, & Asensio-S-Manzanera, 2016). So, marjoram essence analysed here could be this last species, known as Spanish marjoram.…”
Section: Discussionsupporting
confidence: 91%
“…So, an anti-anxiety (Kim, Seo, Min, Park, & Seol, 2014), antimicrobial with application as natural preservative in food packaging (Taqi, Askar, Mutihac, & Stamatin, 2013), anti-inflammatory, antiviral or inhibitory of nuclear factor (NF)-kB effect (Li et al, 2016) could be expected with marjoram essence due to high 1,8-cineol (59.59%) content. Our results are in agreement with the percentages obtained from 20 samples of T. mastichina essential oils (1,8-cineol 56.80-69.60%) from Spain (Delgado et al, 2014), and according with ISO quality standards (Table 4) of T. mastichina (Mendez-Tovar, Novak, Sponza, Herrero, & Asensio-S-Manzanera, 2016). So, marjoram essence analysed here could be this last species, known as Spanish marjoram.…”
Section: Discussionsupporting
confidence: 91%
“…Our results agree with other studies reported for members of Lamiaceae family plants (Martins et al, ; Roby et al, ). Some researchers reported lower rosmarinic acid content (Delgado et al, ; Skendi et al, ). Erturk et al () studied Ocimum bacillicum (sweet basil) and Thymbra spicata from Amasya, Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Alizadeh, Alizadeh, Amari, and Zare () reported FRAP values for Thymus daenensis of 24.23–26.45 µM quercetin equivalent/g for dry weight. In another study, the FRAP values of Thymus mastichina were studied for both essential oil and methanolic extracts, finding that due to the use of a phosphate buffer at pH 6.6, the essential oil underwent phase separation and did not produce proper results (Delgado et al, ). The literature has no FRAP values for zahter essential oil, making our results the first, to best of our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by leaves distributed in opposite pairs and small zygomorphic and bilabiate flowers [24]. It is an endemic thyme with a high added value due to its use as spices and/or medicinal herbs, with several pharmacological properties, such as antispasmodic, antiseptic, antitussive actions [25].…”
Section: Introductionmentioning
confidence: 99%